Image and desire in artistic creation - Salas, Carlos (Estudios de Filosofía, 1997)
From his being an artist, the author aims to reveal a link between image and wish in artistic creation. First, he analyses the relation of artist to wiish. The artist's task, according to him, is to make appear something existing only as illusion; he has to lookfor it though he is certain he wouldfind nothing. This hopeless search that weakens his own being and turns him into his own spectator, is the impulsion proper to wish. So, even befare the work is imagined there is really just a wish, which becomes a work but, as dreams, eludes formalisation. Second, the author points to the relation between wish and spectator. From the assumption that the power of image is in the very inner part of human feeling, and not in any logical or rational view, the author states that there is a connection between spectator and wish: the artist's wish produces various perception possibilities to the spectator who, in his turn, interprets the work according to his own wish.